First record of a macroraptorial sperm whale (Cetacea, physeteroidea) from the miocene of Argentina - Piazza, David Sebastián (2018)
Raptorial sperm whales of the genus Livyatan were described from the Miocene of Peru and Chile. Revision of paleontological collections resulted in the finding of isolated teeth belonging to aff. Livyatan sp. coming from Early-Middle Miocene strata from Bajo del Gualicho area, Río Negro Province, Argentina. These specimens represent the first finding of this genus in the Southwestern Atlantic Ocean and indicate that Livyatan-like forms were more widespread than previously thought. The reasons of the extinction of such predatory whales are still uncertain, but it is not improbable that it may be correlated with competition for food resources with globicephaline delphinids. This hypothesis still rests on weak evidence and should be evaluated through findings of new specimens, as well as detailed analysis of the fossil record.